2003
DOI: 10.1002/jcu.10210
|View full text |Cite
|
Sign up to set email alerts
|

In vitro investigation of detectability of colorectal lymph nodes and diagnosis of lymph node metastasis in colorectal cancer using B‐mode sonography

Abstract: The results of this node-by-node in vitro study show the current limitations and potential of sonography for assessing colorectal lymph nodes. High-frequency sonography may be insufficient for identifying lymph node metastasis in colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…For the lymph node data, the reduced midband fit and intercept of the lymph node data is consistent with the lower echogenicity of malignant nodes relative to benign nodes 45. Intercept has also been shown to be a useful parameter for the differentiation of ex vivo metastatic and nonmetastatic lymph nodes in the context of breast cancer22 and colon cancer 33…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…For the lymph node data, the reduced midband fit and intercept of the lymph node data is consistent with the lower echogenicity of malignant nodes relative to benign nodes 45. Intercept has also been shown to be a useful parameter for the differentiation of ex vivo metastatic and nonmetastatic lymph nodes in the context of breast cancer22 and colon cancer 33…”
Section: Discussionsupporting
confidence: 58%
“…In the context of gastrointestinal cancer, ex vivo studies of lymph node metastases of colorectal cancer have shown that ultrasound backscatter analysis performed better than B-mode ultrasound32 even when multiple B-mode sonographic parameters were considered 33. Our previous in vivo pilot study34 showed that mean spectral parameters computed from EUS RF data can provide a non-invasive method to discriminate normal pancreas from diseased pancreas and benign from malignant lymph nodes.…”
mentioning
confidence: 99%
“…Studies of lymph node metastases of colorectal cancer have shown that ultrasound backscatter analysis performed better than B-mode ultrasound 18 and that even consideration of multiple B-mode sonographic parameters may be insufficient for identifying metastases. 19 To our knowledge, ultrasound spectrum analysis has not been previously used in the arena of EUS.…”
Section: Introductionmentioning
confidence: 99%
“…Some of our previous studies established that a larger node size and a more-spherical (i.e., circular on the B-mode image) node shape are correlated with an increased likelihood of nodal metastasis. 33,34) The Bmode images of N1, N2, and N3 look similar with an obvious fat layer and well-defined speckle patterns throughout the interior of the node. An appreciable, but slight ($4 dB) Table I.…”
Section: Conventional High-frequency Ultrasound Imagesmentioning
confidence: 90%